Plant transcription factors-being in the right place with the right company - Strader, L.; Weijers, D.; Wagner, D.
Transcriptional regulation underlies many of the growth and developmental processes that shape plants as well as their adaptation to their environment. Key to transcriptional control are transcription factors, DNA-binding proteins that serve two essential functions: to find the appropriate DNA contact sites in their target genes; and to recruit other proteins to execute transcriptional transactions. In recent years, protein structural, genomic, bioinformatic, and proteomic analyses have led to new insights into how these central functions are regulated. Here, we review new findings relating to plant transcription factor function and to their role in shaping transcription in the context of chromatin.
Keywords: BINDING SPECIFICITY; CHROMATIN; DNA BINDING; PIONEER TRANSCRIPTION FACTOR; PROTEIN CONDENSATION; TRANSCRIPTION